Cross-border currency exposures: New evidence based on an enhanced and updated dataset - Agustín Bénétrix; Deepali Gautam; Luciana Juvenal; Martin Schmitz (European Central Bank (ECB), 2020)
This paper provides a dataset on the currency composition of the international investment position for a group of 50 countries for the period 1990-2017. It improves available data based on estimates by incorporating actual data reported by statistical authorities and refining estimation methods. The paper illustrates current and new uses of these data, with particular focus on the evolution of currency exposures of cross-border positions.
Keywords: F20; F31; F41; 330; Currency composition; international investment position; foreign currency exposures